Effect Of E-Money Easy And Usefulness On Decisions To Use E-Money In Society (Case Study Of The South Surabaya Community) - Ilham S.A, Adyaldo; Yuliastanti, Rika; Setya, W., Parwita; Utomo, M., Wahjudi (International Publisher (YAPENBI), 2022)
This study examines and analyzes the effect of usefulness and convenience on the decision to use E-Money. This study uses data analysis sourced from primary data by distributing questionnaires to 8 sub-districts in the southern Surabaya area. Method The sample used in this study is cluster sampling and produced 105 samples of respondents. The analytical tool used is multiple linear regression. The results showed that simultaneously the ease and usefulness of E-Money variables influenced the decision to use E-Money, while partially the ease and usefulness of E-Money had a positive effect on the decision to use E-Money, in eight sub-districts of South Surabaya. And the most dominant variable in its influence on the decision to use E-Money is the convenience variable.